Creatine Kinase-MB as a Cardiac Biomarker in Canine Cardiac Disorders - Sagar, Rayala S.; Mudraje, Narayana B.; Chikmagalur, Ansar K.; Siddaraju, Naveen K.; Appaiah, Kshama M.; Sahadev, Annayappa; Rao, Suguna; Panchaxarayya, Kalmath G. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Cardiovascular diseases are the most common causes of death in dogs. Estimation of Creatine Kinase-MB is used for diagnostic andprognostic information in dogs’ case of congestive heart failure. The present study was undertaken to determine the serum concentrationsof the Creatine Kinase-MB isoenzyme in apparently healthy dogs and dogs affected with congestive heart failure and also to distinguish between the stages and duration of congestive heart failure. Creatine Kinase-MB was measured in dogs with cardiac diseases and in apparently healthy dogs. There was a significant increase (p ≤0.01) in the concentration of Creatine Kinase-MB in cardiac disorder in dogs compared to the apparently healthy dogs. Creatine Kinase-MB concentration reached a peak in per-acute, acute and sub-acute stages of the cardiac disorders as compared to the apparently healthy dogs. In CHIEF system, there was a significant (p ≤0.01) increase in the Creatine Kinase-MB in stages B, C1, and C2, and C3 as compared with the apparently healthy dogs and decrease (p ≤0.01) in the Creatine Kinase-MB in stage D as compared to other stages
Keywords: Cardiac disorders; Creatine Kinase-MB; Dogs